1978
DOI: 10.1007/bf00407936
|View full text |Cite
|
Sign up to set email alerts
|

Screening for lignin degrading bacteria by means of 14C-labelled lignins

Abstract: Several Nocardia and Pseudomonas spp., as well as some unidentified bacteria, isolated from lake water containing high loads of waste lignin, were tested for their capacity to release 14CO2 from specifically 14C-labelled dehydropolymer of coniferyl alcohol (DHP) or corn stalk lignins. The bacteria were selected according to their ability to degrade phenolic compounds. However, only some of them could release significant amounts of 14CO2 from the labelled lignin. The tested Nocardia spp. were more active than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 9 publications
1
32
0
3
Order By: Relevance
“…A minority of sequences were similar to members of Rhodococcus, Nocardia and Mycobacterium, which are commonly found in soil and water and include human pathogens, saprophytes (Ryan, 2004) and decomposers able to process complex aromatics (van der Geize and Dijkhuizen, 2004), lignin (Trojanowski et al, 1977;Haider et al, 1978) and complex hydrocarbons such as petroleum distillates (Aislabie et al, 1998).…”
Section: Fungal and Actinobacterial Sequencesmentioning
confidence: 99%
“…A minority of sequences were similar to members of Rhodococcus, Nocardia and Mycobacterium, which are commonly found in soil and water and include human pathogens, saprophytes (Ryan, 2004) and decomposers able to process complex aromatics (van der Geize and Dijkhuizen, 2004), lignin (Trojanowski et al, 1977;Haider et al, 1978) and complex hydrocarbons such as petroleum distillates (Aislabie et al, 1998).…”
Section: Fungal and Actinobacterial Sequencesmentioning
confidence: 99%
“…But the present study confirms that when the coir pith was treated with the mushroom Pleurotus sajor caju, the nutrient content of coir pith such as Nitrogen, Phosphorous and Potassium showed the variation and it get increased. In addition to the fungi, several reports brought strong evidence of some bacteria can degrade lignin effectively (Crawford, 1978;Haider et al, 1978;Kawakami., 1976;Trojanowski et al, 1977). Cullen and Kersten (2004) reported that the enzymes from white rot fungi that catalyse the initial depolymerization of lignin are extra cellular and unusually non specific.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of Actinobacteria and Bacilli from various habitats of the Wadden Sea with different biopolymers shows that these strains are capable of degrading a variety of polymeric substances. Actinobacteria are well known to be able to degrade various polymeric substances such as cellulose and lignin and also rubber and polyester (Haider et al 1978;Godden and Penninckx 1984;Jendrossek et al 1997). F. vesiculosus, cellulose, starch, chitin, and laminarin are typical for coastal marine environments which may explain why Actinobacteria prosper in the Wadden Sea and why they were isolated so frequently.…”
Section: Effects Of Different Substratesmentioning
confidence: 98%